2012
DOI: 10.1111/j.1600-0714.2012.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variants of XRCC1 and XRCC3 repair genes and susceptibility of oral cancer in Brazilian patients

Abstract: These results suggest that allelic variants of XRCC1 and XRCC3 are not suitable markers for susceptibility to carcinomas of the oral cavity and are also not related to the later stages of such tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The distribution of the genotypes of the XRCC1 Arg194Trp, Arg280His, and Arg399Gln polymorphisms in the control groups was consistent with the HWE, except in three of the studies. Two of these studies were related to the Arg194Trp polymorphism [37], [43], and one was related to the Arg399Gln polymorphism [51]. These studies were excluded from the subsequent analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of the genotypes of the XRCC1 Arg194Trp, Arg280His, and Arg399Gln polymorphisms in the control groups was consistent with the HWE, except in three of the studies. Two of these studies were related to the Arg194Trp polymorphism [37], [43], and one was related to the Arg399Gln polymorphism [51]. These studies were excluded from the subsequent analyses.…”
Section: Resultsmentioning
confidence: 99%
“…This finding may have happened by chance, or may have resulted from different gene frequencies in the different populations; the MAF of XRCC1 Arg194Trp is 0.26 for Asians but only 0.09 for Caucasians. A number of studies have reported the association between the XRCC1 Arg194Trp polymorphism and oral cancer risk [10], [39], [41], [43], [44], [51]. It has been reported that the XRCC1 Arg194Trp polymorphism may result in decreased repair efficiency of DNA damage, and the repair deficit may eventually increase an individual's susceptibility to oral cancer [53], [54].…”
Section: Discussionmentioning
confidence: 99%
“…To address this problem, subgroup analysis was conducted in this study by HWE in controls. When the study [13] that significantly deviated from HWE was excluded from this present analysis, we did not observe a substantial modification of the results, suggesting that this factor might not have effects on the overall estimates in the current meta-analysis.…”
Section: Discussionmentioning
confidence: 70%
“…The variant rs861539 in XRCC3 , characterized by a C–T transversion at position 722, affects protein repair function, leading to genetic instability and DNA DSB accumulation (Lindh, Rafii, Schultz, Cox, & Helleday, ; Matullo et al, ; Nowacka‐Zawisza et al, ; Pierce, Johnson, Thompson, & Jasin, ). Previous studies have demonstrated that these genetic variants in RAD51 and XRCC3 contribute to development and progression in acute myeloid leukemia and carcinomas in several locations (Avci, Ergen, Bireller, Ertugrul, & Cakmakoglu, ; Dos Reis et al, ; Farnebo et al, ; Flores‐Obando, Gollin, & Ragin, ). However, their role in oral and oropharyngeal SCC is not well established.…”
Section: Introductionmentioning
confidence: 99%